Improving the Medium-Term Forecasting of Space Weather: A Big Picture Review From a Solar Observer's Perspective - Vourlidas, Angelos (Frontiers in Astronomy and Space Sciences, 2021)
We have improved considerably our scientific understanding of the key solar drivers of Space Weather, i.e., Coronal Mass Ejections, flares, in the last 20+ years thanks to a plethora of space missions and modeling advances. Yet, a major breakthrough in assessing the geo-effectiveness of a given CME and associated phenomena still escapes us, holding back actionable medium-term (up to 7 days) forecasting of Space Weather. Why is that? I adopt a two-pronged approach to search for answers. First, I assess the last 20+ years of research on solar drivers by identifying lessons-learned and paradigm shifts in our view of solar activity, always in relation to Space Weather concerns. Then, I review the state of key observation-based quantities used in forecasting to isolate the choke points and research gaps that limit medium-term forecasting performance. Finally, I outline a path forward along three vectors—breakthrough capabilities, geo-effective potential, and actionable forecast—with the strongest potential to improve space weather forecasting horizon and robustness.